Pengaruh Seminar UMKM Terhadap Minat Siswa Dalam Berwirausaha Studi Kasus: SMK Pgri 1 Pariwisata Cianjur - Somantri, Somantri; Sujjadai, Alun; Putriana, Akfi Tsani; Putri, Andini Wangsa; Benedicta, Octavia; Hermawan, Tina Haerani; Maulana, Riko (PASAI : Jurnal Pengabdian kepada Masyarakat, 2023)
Tridharma is an obligation and responsibility contained in higher education that must be carried out by the entire academic community involved, both lecturers and students, which consists of 3 points, namely: (1) Education and Teaching, (2) Research and Development, (3) Community Service. Community Service is outlined in the form of Real Work Lectures. Researchers conduct research at SMK PGRI 1 Pariwisata Cianjur. The purpose of this study is to find out how much influence the UMKM Seminar has on students' interest in entrepreneurship where students are required to be able to produce a product and market it. With this seminar, it is hoped that students can be motivated to build a business by utilizing technology that is developing today. The method used is multiple linear regression analysis with the number of samples taken by 34 people. The results obtained in this study are that there is a significant influence of the UMKM Seminar on students' interest in entrepreneurship